Castor oil derived poly(urethane urea) networks with reprocessibility and enhanced mechanical properties. (9th May 2018) - Chen, Jia-Hui; Hu, Dan-Dan; Li, Yi-Dong; Meng, Fanlong; Zhu, Jiang; Zeng, Jian-Bing
Abstract: Castor oil (CO) derived polyurethane networks exhibit poor mechanical properties and non-reprocessibility due to flexible, highly and permanently cross-linked network structures. To overcome these defects, we designed and fabricated a series of poly (urethane urea) (PUU) networks by reacting CO-based polyurethane precursor with different amounts of 4-aminophenyl disulfide (APD). The equilibrium swelling behavior, mechanical properties, stress relaxation and reprocessibility of the COPUU networks were investigated in detail in this study. The swelling ratio increased with increasing APD content due to the reduced crosslink density. The mechanical properties of the COPUU networks are tunable over a broad range (either as elastomers or as plastics) depending on the APD component inputs. The tensile strength, Young's modulus and elongation at break for COPUU composed of CO/APD (W/W, 7:3) were improved by 11.7, 2.7 and 5.2 times, respectively, compared to the control CO-based polyurethane without APD. The COPUU can be reprocessed though thermal compression molding and the mechanical properties recovered completely after reprocessing at 180 °C for several cycles. The stress relaxation of COPUU accelerated with increasing APD content due to the increasing concentration of exchangeable disulfide linkage. Graphical abstract: Image 1 Highlights: Poly (urethane urea) was prepared from castor oil and 4-aminophenyl disulfide. Poly (urethane urea) showed excellent strength, ductility and reprocessibility. The stress relaxation of poly (urethane urea) increased with increasing 4-aminophenyl disulfide content.